DevEx: What Actually Drives Productivity? - NODA, ABI; STOREY, MARGARET-ANNE; FORSGREN, NICOLE; GREILER, MICHAELA (Communications of the ACM, 2023)
This article focuses on how to define, measure, and improve software developer productivity by focusing on developer experience (DevEx). The article describes DevEx in detail with a look at each of the core dimensions—feedback loops, cognitive load, and flow state—as well as perceptions, workflows, and key performance indicators (KPIs). The article closes with how DevEX is increasing productivity at an e-commerce company, eBay Inc., and biopharmaceutical company, Pfizer Inc.